2014
DOI: 10.3791/51082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cerebral Autoregulation via Oscillatory Lower Body Negative Pressure and Projection Pursuit Regression

Abstract: The process by which cerebral perfusion is maintained constant over a wide range of systemic pressures is known as "cerebral autoregulation." Effective dampening of flow against pressure changes occurs over periods as short as ~15 sec and becomes progressively greater over longer time periods. Thus, slower changes in blood pressure are effectively blunted and faster changes or fluctuations pass through to cerebral blood flow relatively unaffected. The primary difficulty in characterizing the frequency dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The primary goal of this study was to establish the character of human sympathetic neurovascular control. Although studies have attempted to address this question in humans (14,28,44), precisely whether sympathetic modulation occurs remains controversial with studies reporting discrepant hemodynamic responses to sympathetic blockade (1). The discrepancies between studies have been partly attributed to the use of analytical methods like linear transfer function analysis that assume data linearity and stationarity (14,28,44).…”
mentioning
confidence: 99%
“…The primary goal of this study was to establish the character of human sympathetic neurovascular control. Although studies have attempted to address this question in humans (14,28,44), precisely whether sympathetic modulation occurs remains controversial with studies reporting discrepant hemodynamic responses to sympathetic blockade (1). The discrepancies between studies have been partly attributed to the use of analytical methods like linear transfer function analysis that assume data linearity and stationarity (14,28,44).…”
mentioning
confidence: 99%
“…By the use of oscillatory LBNP, Hamner et al (2004) and Taylor et al (2014) found that the coherence between induced blood pressure oscillations and observed CBFv oscillations was decreasing at frequencies below 0.07 Hz. This phenomenon remained unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of the fast component of autoregulation is generally defined by measurement of the transfer function (TF) from blood pressure to cerebral flow changes. For this measurement, the subject is kept in one position in relation to gravity, for example, lower body negative pressure (LBNP) (Birch et al 2002;Brown et al 2004;Hamner et al 2004;Taylor et al 2014;Smirl et al 2015), standing up from sitting (van Beek et al 2008;Oudegeest-Sander et al 2014), or squat-stand maneuvers (Birch et al 1995;Claassen et al 2009; Barnes et al 2017). No in-depth studies have analyzed the TF when the gravity vector itself is being manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…A second recent review of autonomic neural control of the cerebral vasculature divided up this control into sympathetic and cholinergic control mechanisms, Tan and Taylor (2014). It was concluded that both played a role in autoregulation, although the evidence base is slim, particularly for the former.…”
Section: Neural Controlmentioning
confidence: 99%
“…Projection pursuit regression (PPR) was used by Taylor et al (2014) in conjunction with oscillatory LBNP testing to quantify the non-linear relationship between ABP and CBFV. Projection pursuit regression (PPR) was used by Taylor et al (2014) in conjunction with oscillatory LBNP testing to quantify the non-linear relationship between ABP and CBFV.…”
Section: Non-linear Analysismentioning
confidence: 99%